La composición de la producción agropecuaria en el Valle Central costarricense. Un estudio comparativo de las regiones de oriente y occidente 1785-1805 - Alvarenga Venutolo, Patricia (1987)
Costa Rica´s Central Valley underwent a major economic growth cycle during the late Colonial period. However, the effect of this growth on socio-economic structures was not homogeneous, and there were noticeable discrepancies between the eastern and western sections of that Valley. In the former, adverse conditions faced be direct producers did not allow them to benefit from mercantile expansion, as did those living in the western section.